18F-FDG PET/CT as a central tool in the shift from chronic Q fever to Coxiella burnetii persistent focalized infection: A consecutive case series. Issue 34 (August 2016) - Eldin, Carole; Melenotte, Cléa; Million, Matthieu; Cammilleri, Serge; Sotto, Albert; Elsendoorn, Antoine; Thuny, Franck; Lepidi, Hubert; Roblot, France; Weitten, Thierry; Assaad, Souad; Bouaziz, Anissa; et al.
Abstract : Abstract: Because Q fever is mostly diagnosed serologically, localizing a persistent focus of Coxiella burnetii infection can be challenging. 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) could be an interesting tool in this context. We performed a retrospective study on patients diagnosed with C burnetii infection, who had undergone 18 F-FDG PET/CT between 2009 and 2015. When positive 18 F-FDG PET/CT results were obtained, we tried to determine if it changed the previous diagnosis by discovering or confirming a suspected focus of C burnetii infection. One hundred sixty-seven patients benefited from 18 F-FDG PET/CT. The most frequent clinical subgroup before 18 F-FDG PET/CT was patients with no identified focus of infection, despite high IgG1 serological titers (34%). For 59% (n = 99) of patients, a hypermetabolic focus was identified. For 62 patients (62.6%), the positive 18 F-FDG PET/CT allowed the diagnosis to be changed. For 24 of them, (38.7%), a previously unsuspected focus of infection was discovered. Forty-two (42%) positive patients had more than 1 hypermetabolic focus. We observed 21 valvular foci, 34 vascular foci, and a high proportion of osteoarticular localizations (n = 21). We also observed lymphadenitis (n = 27), bone marrow hypermetabolism (n = 11), and 9 pulmonary localizations. We confirmed that 18 F-FDG PET/CT is a central tool in the diagnosis of C burnetii focalized persistent infection. We proposed new diagnostic scores for 2 main clinical entities identified using 18 F-FDG PET/CT: osteoarticular persistent infections and lymphadenitis. Abstract : Supplemental Digital Content is available in the text